Revision of the New Caledonian endemic genus Bohumiljania Monrós (Coleoptera: Chrysomelidae: Spilopyrinae) - Reid, C. A. M.; Beatson, M. (Zootaxa, 2011)
The chrysomelid genus Bohumiljania Monrós, 1958, is revised, with nine species, seven new: B. aoupinie sp. nov., B. caledonica (Jolivet, 1957), B. lafoa sp. nov., B. humboldti Jolivet, Verma & Mille, 2005, B. mandjelia sp nov., B. tango sp. nov., B. xanthogramma sp. nov., B. xaracuu sp. nov., B. yuaga sp. nov. All species are described. The type species, B. caledonica, is shown to have been misidentified in recent literature. The original description of the other described species, B. humboldti, is shown to include at least three species. A key is provided for identification of Bohumiljania species, all of which are endemic to the main island of New Caledonia. Six of the species are known from just 14 specimens, suggesting that further species remain to be discovered. The morphology and biology of Bohumiljania is reviewed, including description of the larva.